The arabic and turkish lexic in the written monument «Kitab Bulgat al-Mushtaq» - Mustafayeva А. (Journal of Oriental Studies, 2022)
In the preservation and development of the modern Turkic languages, one of the key roles belongs to linguistic written monuments, as carriers of not only the language, but also the mentality, made during the reign of the Mamluk Kipchaks in Egypt and Syria, in particular the bilingual dictionary of the 14th century Kitab Bulgat al-Mushtak. First, the manuscript is one of six found works; secondly, if the verb part of the monument was studied in Kazakh Turkology, then the nominal part was practically not consid- ered; thirdly, the manuscript is kept in a single copy in France, which is more difficult in comparison with access to the archival and library funds of other countries (Russia, Turkey, Uzbekistan, etc.) during a pan- demic; fourthly, the peculiarities of the dictionary itself arouses the interest of the researcher: the form of a zigzag form of writing style, the presence of lexical units that are not found in the other five works, etc. The material received from France on the basis of a copy of the manuscript provided access to the lexical fund of the work, namely, it made it possible to identify, write, read and translate from Arabic and Kypchak languages into Kazakh. By studying the Turkic lexis of the monument, it is possible to de- termine the share of the Old Kipchak language vocabulary in modern Turkic languages, incl. in Kazakh. Key words: Turki, Kipchak, Mamluk, al-Mushtaq, lexis, Arabic, written monument.